The Need to Belong in Secondary School A Social Work Science Study of Austrian and Australian Students - du Plessis-Schneider, Sharon (Verlag Barbara Budrich, 2022)
Our social interactions are driven by complex biopsychic processes that are complicated by the fact that humans are individuals and at the same time members of one or more social systems, such as schools. This book contributes to explaining the social mechanisms influencing students' "need to belong" fulfilment at school. The theoretical framework is informed by human needs understood as cognitive mechanisms of neural processes that regulate human behaviour and bio-values. The fieldwork was conducted in two secondary schools in Austria and Australia. Based on the findings, the transformative three-step approach suggests a course of action for student belonging.